Development and Design of a Microcontroller-Based Gas Weight and Leakage Detection System - Fagbohun, O.; Fagbohun, O.; Obiyemi, O.; Moloi, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This paper presents the design and development of a prototype system for monitoring gas leakage and weight in residential and semi-commercial. Liquid Petroleum Gas (LPG) installations LPG is widely used as a fuel source, but its leakage can lead to devastating fires, posing a significant threat to life and properties. Traditional methods of gas management based on natural nasal detection and estimation of usage are considered unsafe. The proposed system incorporates the MQ-5 sensor for gas leakage detection and the HX711 IC device for weight sensing. It includes a user alert system with a buzzer and LED for timely notifications of gas leakage and low gas levels. The control system, driven by the ATMega328p microcontroller, receives data from the sensors and triggers alerts accordingly. The power unit utilizes a 3.7-volts amplified lithium polymer battery stepped up by the MT3608. The results show that through week-long testing, the prototype demonstrated its effectiveness in monitoring weight and gas leakage, with constant monitoring of sound, LED, and display readings. This paper offers insights for replication as students projects, and suggests the need for more testing and calibration to ensure safety and the need for IoT-enabled features for smarter deployment and management. Furthermore, the prototype had contributed to promoting safety and preventing accidents in LPG installations by addressing the critical issue of gas leakage.